Sodium dodecyl sulfate intercalated two-dimensional nickel-cobalt layered double hydroxides to synthesize multifunctional nanomaterials for supercapacitors and electrocatalytic hydrogen evolution. (1st February 2023) - Zhang, Mengyang; Zhou, Wending; Yan, Xuehua; Huang, Xinpeng; Wu, Sutang; Pan, Jianmei; Shahnavaz, Zohreh; Li, Tie; Yu, Xiyang
Graphical abstract: A dual-function electrode with nanometer hierarchical structure has been developed to obtain anionic (SDS) intercalated CoNi-LDH nanosheets, which possess excellent electrochemical properties and electrocatalytic hydrogen evolution. Highlights: Anion (SDS) intercalation CoNi-LDH has defect-rich hierarchical structure. The defects are formed through anion redistribution and nucleation of Ni 2+ /Co 2+ . The electrode retains 91% capacity after 10, 000 cycles under high current density. The energy storage mechanism is revealed via combining multi-characterizations. The electrode for HER at 181 mV shows superior performance retention rate of 98.1%. Abstract: The controllable adjustment of layered double hydroxide layer spacing makes it possible as electrode material for energy storage and electrochemical hydrogen evolution at the same time. However, the lower conductivity and agglomeration significantly hinder its large-scale application as an active electrode material. Here, sodium dodecyl sulfate (SDS) intercalation modification was used to construct LDH derivatives and CoNi-SDS-LDH nanosheets were grown vertically on the nickel foam (NF) surface using in situ growth technique to construct a layered structure of nanosheets supported by nanowires, which effectively enhanced the ion transport efficiency and greatly reduced the agglomeration phenomenon of nanosheets. Thanks to the charge rearrangement in LDH and the controlled defects of the nanosheets, the electrode material has good electrochemical performance. The cycling stability of the CoNi-SDS-LDH self-supported electrode material is 91% after 10, 000 cycles at 5 A g −1 . Notably, the electrode material showed 98.1% performance retention after 10 h of hydrogen evolution test. It is shown that the anionic modification offers the possibility for large-scale applications of LDH in flexible supercapacitors and electrocatalytic hydrogen precipitation.